La produccion artesanal de semilla de frijol - Rodriguez, E.=700 1 Palma, Q.; Lorenzo, E.
(En, Es)
ilus., 8 ref.
Keywords: PHASEOLUS VULGARIS; PRODUCCION DE SEMILLAS; FITOMEJORAMIENTO; CARACTERISTICAS AGRONOMICAS; PANAMA; COSTA RICA